Management of Psoriatic Arthritis in Patients With Comorbidities: An Updated Literature Review Informing the 2021 GRAPPA Treatment Recommendations - DURUÖZ, MEHMET TUNCAY (My University, 2023)
Objective. The 2021 Group for Research and Assessment of Psoriasis and Psoriatic Arthritis (GRAPPA) treatment recommendations provide an evidence-based guide for selecting therapy based on the individual’s disease features. Beyond the disease features and associated conditions (eg, uveitis and inflammatory bowel disease), comorbidities play an important role in selecting therapy for an individual patient. Methods. We performed a systematic literature review. We examined the available evidence to inform treatment selection based on the presence or absence of comorbidities in psoriatic arthritis (PsA). Results. Common comorbidities in PsA that may affect treatment selection include presence of baseline cardiovascular disease (CVD) or high risk for CVD, obesity and metabolic syndrome, liver disease, mood disorders, including depression in particular, chronic infections, malignancies, osteoporosis, and fibromyalgia and/or central sensitization. Conclusion. Comorbidities may influence both the effectiveness of a given therapy but also the potential for adverse events. It is important to assess for the presence of comorbidities prior to therapy selection.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; İmmünoloji; ALERJİ; ROMATOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; IMMUNOLOGY; ALLERGY; RHEUMATOLOGY; Romatoloji; İmmünoloji ve Alerji; Rheumatology; Immunology and Allergy; Immunology; comorbidities; GRAPPA; psoriatic arthritis; treatments